Tensor-based morphometry and stereology reveal brain pathology in the complexin1 knockout mouse. - Catherine Kielar (Public Library of Science (PLoS), 2012)
Complexins (Cplxs) are small, soluble, regulatory proteins that bind reversibly to the SNARE complex and modulate synaptic vesicle release. Cplx1 knockout mice (Cplx1(-/-)) have the earliest known onset of ataxia seen in a mouse model, although hitherto no histopathology has been described in these mice. Nevertheless, the profound neurological phenotype displayed by Cplx1(-/-) mutants suggests that significant functional abnormalities must be present in these animals. In this study, MRI was used to automatically detect regions where structural differences were not obvious when using a traditional histological approach. Tensor-based morphometry of Cplx1(-/-) mouse brains showed selective volume loss from the thalamus and cerebellum. Stereological analysis of Cplx1(-/-) and Cplx1(+/+) mice brain slices confirmed the volume loss in the thalamus as well as loss in some lobules of the cerebellum. Finally, stereology was used to show that there was loss of cerebellar granule cells in Cplx1(-/-) mice when compared to Cplx1(+/+) animals. Our study is the first to describe pathological changes in Cplx1(-/-) mouse brain. We suggest that the ataxia in Cplx1(-/-) mice is likely to be due to pathological changes in both cerebellum and thalamus. Reduced levels of Cplx proteins have been reported in brains of patients with neurodegenerative diseases. Therefore, understanding the effects of Cplx depletion in brains from Cplx1(-/-) mice may also shed light on the mechanisms underlying pathophysiology in disorders in which loss of Cplx1 occurs.